On the arboreal Afrotropical ant-mimicking castianeirine spider genus Castianeirodes Strand, 1916 (Araneae: Corinnidae) - Haddad, Charles R. (Zootaxa, 2026)
The genus Castianeirodes Strand, 1916, with C. insulicola (Strand, 1916) comb. nov. (ex Castianeira Keyserling, 1879) from D.R. Congo as the type species, is revalidated and formally described and diagnosed for the first time. The female holotype of C. insulicola is redescribed and illustrated for the first time; the male remains unknown. Three new species are described from both sexes: C. jocquei sp. nov. from Ghana, C. kakamega sp. nov. from Kenya and C. natalensis sp. nov. from South Africa.